West Indian Folk Music Analysis (International Journal of Engineering and Computer Science, 2017)
This paper extract the features of folk music of west region of India with consideration of elements of music such as duration, dynamics, harmony, melody, structure, texture and timbre of folk songs. This paper also helps to improve the performance of the folk songs.